Pragmatic-Functional Importance of Translation of Titles and Headlines in Popular Science Texts - Tadjibayev, Muzaffar (Pubmedia Social Sciences and Humanities, 2024)
This article discusses the role and importance of titles and headlines in the structure of the general text, its pragmatic-functional tasks in ensuring the success of the text. The linguistic elements perform pragmatic function. The opinions of famous linguists on the titles and headlines, its structure and pragmatic functions are cited. Functions and syntactic models of titles and headlines are presented. Examples of popular science text titles, headlines and their translations into Uzbek and Russian are presented and analyzed.